2021
DOI: 10.1021/acs.jmedchem.1c00611
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dual-Target μ-Opioid Receptor and Dopamine D3 Receptor Ligands as Potential Nonaddictive Pharmacotherapeutics for Pain Management

Abstract: The need for safer pain-management therapies with decreased abuse liability inspired a novel drug design that retains μ-opioid receptor (MOR)-mediated analgesia, while minimizing addictive liability. We recently demonstrated that targeting the dopamine D3 receptor (D3R) with highly selective antagonists/partial agonists can reduce opioid self-administration and reinstatement to drug seeking in rodent models without diminishing antinociceptive effects. The identification of the D3R as a target for the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 66 publications
0
44
0
Order By: Relevance
“…This is in contrast to previously reported and highly D 3 R selective antagonists and partial agonists. , Importantly, this study provides the necessary SAR to position long linker chains and/or sterically bulky groups on the eticlopride molecule to create bioconjugate D 2 R/D 3 R tools of interest such as fluorescent ligands and Drugs Acutely Restricted by Tethering (DARTs) . Further, the design of novel dual target mu opioid receptor and D 3 R partial agonists as potentially nonaddictive analgesics has already been inspired by these novel eticlopride ligands …”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to previously reported and highly D 3 R selective antagonists and partial agonists. , Importantly, this study provides the necessary SAR to position long linker chains and/or sterically bulky groups on the eticlopride molecule to create bioconjugate D 2 R/D 3 R tools of interest such as fluorescent ligands and Drugs Acutely Restricted by Tethering (DARTs) . Further, the design of novel dual target mu opioid receptor and D 3 R partial agonists as potentially nonaddictive analgesics has already been inspired by these novel eticlopride ligands …”
Section: Discussionmentioning
confidence: 99%
“…Allosteric ligands at the MOR could be also interesting as they could be used to enhance the effects of either the exogenous orthosteric agonists when administrated together or the endogenous opioid peptides released in stress or pain condition ( 49 ). Another strategy could be the development of dual-target ligands directed to both MOR and another receptor, including for instance dopamine D3 receptor ( 50 ). Whether biased ligands, ligands with low selectivity toward different opioid receptors, or bivalent ligands, the development of an analgesic compound free of side effects and with low abuse potential seems to be a way still paved with some difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al demonstrated feasibility of targeting MOR/D 2 -likeRs heterodimers by long molecules containing alkaloid MOR-related fragments (naltrexone, hydromorphone) [ 68 ]. Bonifazi et al synthesized MOR-D 3 R bitopic/bivalent compounds in which opioid fragment was based on acyclic opioids [ 75 ].…”
Section: Fentanyl-based Mtas Targeting Mor and D 2 ...mentioning
confidence: 99%
“…As a side note, let us mention that an avenue that might deserve exploration is using fentanyl scaffold for designing compact (‘merged’) MOR/D 4 R multifunctional drugs. Fentanyl ( 1.1 ) has been recently shown to have almost no D 2 R (K i = 21,000 nM) and no D 3 R binding (K i = 26,200 nM), but some moderate, submicromolar affinity for D 4 R (K i = 554 nM) [ 75 ].…”
Section: Fentanyl-based Mtas Targeting Mor and D 2 ...mentioning
confidence: 99%